Lateral Basal Approach to CPA in Supine No-Retractor Method: Microvascular Decompression for Hemifacial Spasm - Shimizu, Katsuyoshi (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives In this video, we demonstrate our more basal approach in microvascular decompression for hemifacial spasm.Design The patient is in supine position with the head rotated maximally to the opposite side on the U-shaped head rest. The small cranial window is made at the lateral bottom of occipital cranium with the adequate superficial manipulation on the muscles layers in the craniocervical junction.Results The more basal approach enables the surgeon to access all the segments of the VIIth nerve tract without cerebellar retraction by spatula, especially in the case with vertebral artery associated compression.Conclusion This approach safely provides the ideal operative corridor promising sufficient decompression in micorvascular decompression for the VIIth nerve.The link to the video can be found at: https://youtu.be/_nKSjGEHoB4.
Keywords: more basal approach; interlaminal fatty layer; skull base; hemifacial spasm; microvascular decompression